PENGARUH RASIO LIKUIDITAS, LEVERAGE, AKTIVITAS, PROFITABILITAS DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS (Studi Kasus pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016) - QURROTUL AINI, DWI; PURWOHANDOKO, (Jurnal Ilmu Manajemen (JIM), 2018)
Thise study aims to analyze the effect of liquidity, leverage, activity, profitability and sales growth ratios on financial distress in mining sector companies listed on the Indonesia Stock Exchange for the period 2012-2016. This type of research data is secondary data obtained from IDX. This study uses liquidity, leverage, activity, profitability and sales growth ratios to predict financial distress. The sample of this study were 35 Indonesian mining sector companies selected using purposive sampling. The analytical method used in this research is logistic regression analysis. The results showed that liquidity, activity and sales growth did not affect financial distress. Leverage and Profitability negatively affect financial distress. Liquidity does not affect financial distress because the size of the liquidity obtained by the company does not affect the occurrence of financial distress. Activities have no effect on financial distress because the size of the activity of the company is not able to influence financial distress and sales growth has no effect because the increase or decrease in sales obtained by the company will not influence the possibility of the company experiencing financial distress. Profitability has a negative effect because the higher the profits obtained by the company will make it easier to manage the company and leverage has a negative effect because companies that have high leverage and the interest expense borne are also higher but if the company is able to fulfill the company will not have difficulty paying so the company will avoid financial distress. Keywords: financial distress; financial ratio; sales growth